Epidemiological and clinical characteristics of dengue fever in Fuzhou, China, in 2023 - Jin Huang; Meiquan Zhang; Shengzhong Li; Jianshuai Liu; Xiong Lin; Qing Li; Jiawei Chen (BMC Infectious Diseases)
Abstract Background This study aimed to analyze the epidemiological and clinical characteristics of dengue fever (DF) in Fuzhou, the capital city of Fujian Province, southeast China. Methods A retrospective analysis was performed on 251 cases of DF diagnosed at the fever clinic of the Second Affiliated Hospital of Fujian University of Chinese Medicine in Fuzhou City, Fujian Province. Epidemic characteristics, such as the number of cases, age distribution, sex distribution, seasonal distribution, and spatial distribution in each region, were analyzed. The patients’ clinical manifestations, signs, auxiliary examinations, and prognoses were analyzed. Results The age distribution of DF cases was mainly concentrated in 30–39 years (20.72%) and 50–59 years (21.12%). There were no sex differences among the patients. Of these cases, 60.16% were concentrated on the lower floors, with retirees having the highest proportion. The seasonal peak of DF in Fuzhou area was from September to November. The SDE plot showed that the cases were mainly concentrated in Jin’an and Gulou districts. Etiological tests revealed serum NS1 antigen (97.61%), serum IgM antibody (15.14%), and serum IgG antibody (0.40%). There were no significant differences in clinical manifestations between the children’s and non-children’s groups. Laboratory tests have shown that the disease is prone to multi-system dysfunction, including the blood system, digestive system, urinary system and internal environment. ROC curve analysis showed that WBC, N, LY, PLT, and CRP levels had specific diagnostic values for DF. Conclusions The epidemiological situation and clinical characteristics of DF in Fuzhou City were analyzed to guide the formulation of reasonable prevention and treatment measures.